Characterization of multidrug resistant ESBL-producing Escherichia coli isolates from hospitals in Malaysia - Lim, K.; Yasin, R.; Yeo, C.; Puthucheary, S.; Thong, Kwai Lin (Hindawi Publishing Corporation, 2009)
The emergence of Escherichia coli that produce extended spectrum beta-lactamases (ESBLs) and are multidrug resistant (MDR) poses antibiotic management problems. Forty-seven E. coli isolates from various public hospitals in Malaysia were studied. All isolates were sensitive to imipenem whereas 36 were MDR (resistant to 2 or more classes of antibiotics). PCR detection using gene-specific primers showed that 87.5% of the ESBL-producing E. coli harbored the blaTEM gene. Other ESBL-encoding genes detected were blaOXA, blaSHV, and blaCTX-M. Integron-encoded integrases were detected in 55.3% of isolates, with class 1 integron-encoded intI1 integrase being the majority. Amplification and sequence analysis of the 5'CS region of the integrons showed known antibiotic resistance-encoding gene cassettes of various sizes that were inserted within the respective integrons. Conjugation and transformation experiments indicated that some of the antibiotic resistance genes were likely plasmid-encoded and transmissible. All 47 isolates were subtyped by PFGE and PCR-based fingerprinting using random amplified polymorphic DNA (RAPD), repetitive extragenic palindromes (REPs), and enterobacterial repetitive intergenic consensus (ERIC). These isolates were very diverse and heterogeneous. PFGE, ERIC, and REP-PCR methods were more discriminative than RAPD in subtyping the E. coli isolates.